Development of Variations in Greetings Before and After Learning the Moral Character of Students in Elementary Schools - M. Iqbal Arrosyad; Fandi Nugroho (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2020)
The development of various greetings before and after learning is made to provide additional references and treatment from teachers to students in interesting learning. The purpose of this study was to describe the development of a variety of greetings before and after learning in Public Alementary Cchool 5 Mendo Barat. The research method used is the Research and Development method with the Thiagarajan Four-D development model which consists of four stages of research, namely (1) defining, including initial analysis, student analysis, concept analysis, and formulation of learning objectives; (2) planning (design) media selection, format selection, and preparation of various greeting media before and after learning; (3) development, including expert validation and testing; and (4) disseminate, including reproduction, socialization, and reflection. The results of this research. The definition stage 1) there is no media variation of greetings before and after learning; 2) lack of student moral character, and 3) teachers do not have information or references related to variations in greetings before and after learning. Researchers began to design a variety of greeting media with preface, table of contents, contents, author's biography, and back cover, on A4 paper size and 12 pt Garamond font. The variety of media greetings before and after learning resulted from the teacher's response to 93.33% of the process. It can be seen from the greeting activities before and after learning the moral character of students. The moral character is not indifferent when invited to discuss, resulting in 60% of the 20 students, the character of piety including a sense of responsibility and good cooperation of the students as much as 60%, the character of polite and respectful with students greeting by shaking hands every time they go to school, speaking politely 70% of teachers and friends, the character of manners in the form of like to help friends if asked for help as much as 70%.